Enzymatic degradation of RNA causes widespread protein aggregation in cell and tissue lysates. (18th September 2020) - Aarum, Johan; Cabrera, Claudia P; Jones, Tania A; Rajendran, Shiron; Adiutori, Rocco; Giovannoni, Gavin; Barnes, Michael R; Malaspina, Andrea; Sheer, Denise
Abstract: Most proteins in cell and tissue lysates are soluble. We show here that in lysate from human neurons, more than 1, 300 proteins are maintained in a soluble and functional state by association with endogenous RNA, as degradation of RNA invariably leads to protein aggregation. The majority of these proteins lack conventional RNA‐binding domains. Using synthetic oligonucleotides, we identify the importance of nucleic acid structure, with single‐stranded pyrimidine‐rich bulges or loops surrounded by double‐stranded regions being particularly efficient in the maintenance of protein solubility. These experiments also identify an apparent one‐to‐one protein‐nucleic acid stoichiometry. Furthermore, we show that protein aggregates isolated from brain tissue from Amyotrophic Lateral Sclerosis patients can be rendered soluble after refolding by both RNA and synthetic oligonucleotides. Together, these findings open new avenues for understanding the mechanism behind protein aggregation and shed light on how certain proteins remain soluble. Synopsis: This study shows that RNA plays an important and direct role in maintaining protein solubility and preventing protein aggregation. More than 1, 300 proteins aggregate when RNA is degraded in neuronal cell lysate. 70% of these proteins lack known RNA‐binding domains. Several proteins linked to neurodegeneration, such as TDP‐43, Huntingtin, and neurofilament, aggregate upon RNA‐degradation. Protein aggregation can be prevented by structured oligonucleotides. . Abstract : This study shows that RNA plays an important and direct role in maintaining protein solubility and preventing protein aggregation.